Backbone modifications in peptidic inhibitors of flaviviral proteases - Jakob, Alexander; Sundermann, Tom R.; Klein, Christian D. (Bioorganic & medicinal chemistry letters, 2019)
The NS2B-NS3 protease is a promising target for the development of drugs against dengue virus (DENV), West Nile virus (WNV) and related flaviviruses. We report the systematic variation of the peptide backbone of the two lead compounds Bz-Arg-Lys-d-Phg-NH2 and Bz-Arg-Lys-d-Phg(OBn)-NH2. While inhibitory activity against WNV protease was generally decreased, the inhibitory potency against DENV protease could be conserved and increased in several peptidomimetics, particularly in those containing a (NMe)arginine fragment or an N-terminal α-keto amide. Methylation at the α-position of the C-terminal phenylglycine led to a 6-fold higher potency against DENV protease. Peptidomimetics with modified backbone showed increased resistance against hydrolytic attack by trypsin and α-chymotrypsin.